2005
DOI: 10.1007/s00125-005-1811-6
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial regulation of insulin production in rat pancreatic islets

Abstract: Aims/hypothesis: The study was designed to identify the key metabolic signals of glucose-stimulated proinsulin gene transcription and translation, focusing on the mechanism of succinate stimulation of insulin production. Methods: Wistar rat islets were incubated in 3.3 mmol/l glucose with and without esters of different mitochondrial metabolites or with 16.7 mmol/l glucose. Proinsulin biosynthesis was analysed by tritiated leucine incorporation into newly synthesised proinsulin. Preproinsulin gene transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
(56 reference statements)
0
11
1
Order By: Relevance
“…3a). Compared with the effects observed by Leibowitz et al [16], who tested 3-NPA in rat islets and observed complete inhibition of glucose-induced hyperpolarisation of Δψ m , the effect of 3-NPA was less pronounced in our experiments. This discrepancy might be due to the experimental design: we switched between 15 and 0.5 mmol/l glucose whereas Leibowitz et al [16] compared the effect of 3-NPA on Δψ m at 16.7 and 3 mmol/l glucose (levels at which respiratory chains are already partly activated).…”
Section: Mitochondrial Function and [Cacontrasting
confidence: 97%
See 1 more Smart Citation
“…3a). Compared with the effects observed by Leibowitz et al [16], who tested 3-NPA in rat islets and observed complete inhibition of glucose-induced hyperpolarisation of Δψ m , the effect of 3-NPA was less pronounced in our experiments. This discrepancy might be due to the experimental design: we switched between 15 and 0.5 mmol/l glucose whereas Leibowitz et al [16] compared the effect of 3-NPA on Δψ m at 16.7 and 3 mmol/l glucose (levels at which respiratory chains are already partly activated).…”
Section: Mitochondrial Function and [Cacontrasting
confidence: 97%
“…Leibowitz et al [16] showed that for rat islets, SDH inhibition by 3-nitropropionic acid (3-NPA) or fumaric acid monoethyl ester (MEF) impaired insulin secretion by lowering gene transcription of preproinsulin and synthesis of proinsulin [16]. As a structural analogue of succinate, 3-NPA covalently and irreversibly binds to the active site of the enzyme thereby preventing complex-II-mediated FADH 2 generation [17].…”
Section: Introductionmentioning
confidence: 99%
“…rescence of a cationic probe such as TMRM (173,183), or the more slowly equilibrating rhodamine 123 (R123) (135,286,304). This technique is complicated by the plasma membrane potential, ⌬ p , which controls the gradient of the probe between the incubation medium and the cytosol.…”
Section: Mitochondrial Membrane Potential (⌬ M )mentioning
confidence: 99%
“…Bearing in mind that the unstimulated ␤-cell maintains an unusually low ⌬G p , could protein synthesis be directly controlled by the phosphorylation potential? Leibowitz et al (286) observed that the cell-permeant monomethyl succinate produced a hyperpolarization of the in situ rat islet mitochondria, and enhanced insulin secretion, to an extent comparable to that with elevated glucose. [ 3 H]leucine incorporation into proinsulin was enhanced by both high glucose and monomethyl succinate, and the authors proposed a direct bioenergetic role for succinate, with a raised ⌬G p as a proximal signal for proinsulin biosynthesis.…”
Section: Insulin Biosynthesismentioning
confidence: 99%
“…The mitochondrial metabolite, succinate, is a key metabolic mediator of glucose-stimulated preproinsulin gene transcription and translation (43). Therefore, we examined mitochondrial function in V5-treated islets and found that mitochondrial function was increased by ϳ42% compared with untreated islets.…”
Section: V5 Allows Single-donor Islet Transplantationmentioning
confidence: 99%